Phytochemical Screening, Pharmacognostic Characterization, Antioxidant Activity, and Hepatoprotective Effects of Abroma augustum (L.) L.f. on Human Hepatocellular Carcinoma (HepG2) Cells and Goat Liver Homogenate - Sandipan Das; Tanushree Deb; Filomena Mottola; Nithar Ranjan Madhu; Yogisharadhya Revanaiah; Israel Maldonado Rosas; Sarbani Dey Ray; Shubhadeep Roychoudhury (Antioxidants)
Abroma augustum (L.) L. f. is characterized by its fibrous structure, spiny trichomes, and distinctive leaf formations, which collectively contribute to its unique morphology and potential medicinal applications. This study aims to investigate the phytochemical constituents and elucidate the pharmacognostic and physicochemical characteristics of the stem bark powder, including evaluation of its antioxidant capacity and hepatoprotective effects against carbon tetrachloride (CCl4)-induced hepatotoxicity in both in vitro and ex vivo experimental models. Comprehensive phytochemical screening identified 50 distinct phytochemicals, including a range of alkaloids, flavonoids, terpenes, phenolics, and coumarins, among others. The extract displayed substantial solubility, with total phenolic and flavonoid content quantified as 12.32 ± 0.01 mg/g and 42.14 ± 3.5 mg/g, respectively. The antioxidant activity revealed IC50 values obtained from 2,2-diphenyl-1-picrylhydrazyl (DPPH), ferric reducing antioxidant power (FRAP), and 2,2′-azinobis-(3-ethylbenzothiazoline-6-sulfonic) acid (ABTS), measured at 214.007 µg/mL, 132.307 µg/mL, and 45.455 µg/mL, respectively. Additionally, the methanolic extract exhibited significant hepatoprotective properties, with observable reductions in lipid peroxidation and decreased concentrations of liver damage biomarkers (ALT, AST, and LDH) in both HepG2 cells and goat liver homogenate. Future investigations are warranted to elucidate the underlying mechanisms of these effects, including histopathological examinations and biochemical assays, followed by the administration of plant methanolic extracts.